Enhanced QoS routing protocol using maximum flow technique. (January 2021) - Alghamdi, Turki Ali
Abstract: Sensor nodes in wireless sensor networks (WSNs) are capable of sensing the surrounding conditions and transferring data to other nodes in the network. These nodes have limited capacity of in-out data transmission period. So to improve the flow, it becomes necessary to route data efficiently. As the network is self-organized, several security threats are presented to WSNs. In this paper, secure and efficient routing protocol applying Maximum Flow Technique (MFT) is proposed. This technique involves security alongside malicious attacks as well as utilizes the bandwidth efficiently to improve the Quality of Service (QoS). The presented approach is validated by using Network simulator (NS2). Graphical abstract: Image, graphical abstract